DIFFICULTIES OF SPEAKING THAT ARE ENCOUNTERED BY ENGLISH LANGUAGE STUDENTS AT AL MARGEB UNIVERSITY - Mohamed Dalem (Premise: Journal of English Education and Applied Linguistics, 2017)
The aim of this paper is to explore the speaking difficulties encountered by English language students at Al Margeb University, and to discover the causes of such difficulties. Speaking English has been a vital importance in international communication. Speaking fluent English is a common problem among the nonnative speakers. The second language learners have gone through a variety of cases to learn how to speak not only correct grammar and using the right vocabulary but with correct accent and pronunciation. Many obstacles, therefore, have been known as the predictors of such a problem among the language learners.  According to the review of literature, appropriate speaking instruction was found to be the learners' priority and a field in which they need more attention. In this paper the writer highlight the speaking difficulties encountered by English language students at Al Margeb University, which are considered to be the most urgent for every teacher, such as fear of mistakes, shyness, anxiety, lack of confidence and lack of motivation. This paper can be useful to teachers to consider their language learners' speaking needs in English language teaching and learning context.